Laparoendoscopic rendez-vous: a safe alternative to the treatment of choledocholithiasis - Kreve, Fernanda (2017)
The choice treatment for choledocholithiasis when associated with lithiasic cholecystitis is endoscopic retrograde cholangiopancreatography (ERCP). However, in some cases this therapeutic fails, which requires an alternative method to extract the stones. The surgical approach tends to be the next step, but it is related to greater complexity of achievement and higher complications rates. In 1993, Deslandres et al. developed the combined treatment called laparoendoscopic rendezvous, that unites in a single stage the endoscopic treatment of choledocholithiasis and laparoscopic removal of the gallbladder. We report the case of a patient diagnosed with common bile duct (CBD) stones, in which the conventional CPRE was not successful, and was taken to treatment by laparoendoscopic approach. We conclude, based on this case and on other published studies, that this therapeutic modality has advantages for being feasible, presenting low complications rate, shorter hospital stay and acceptable cost.